The transformation of Islamic art during the Sunni revival - Tabbaa, Yasser (Publications on the Near East, 2002)
Major developments occurred in the field of Islamic art during the 11th & 12th centuries. In this text, Tabbaa examines the semiotic interplay between history & art, challenging the methodologies of many historians of Islamic art